How music can help teaching the English language to teenagers - Borges, Douglas Tessaro (My University, 2019)
This work has as central theme the use of music to learn the English language, but mainly in how can music be used as a teaching tool of vocabulary by teachers. Teaching through activities with music allows to contextualize and give meaning to learning, because the student will realize that the music, he is studying at school is the same as he hears on the radio or on television, that the English language is no longer a meaningless matter. The methodology used in this paper was be descriptive, with the main objective to describe how the teacher can use music to teach new vocabulary. The discussion shows that music may be a great tool to combine fun and learning, especially considering the reality of public schools in Brazil (sic).
Este trabalho tem como tema central o uso da música para aprender a língua inglesa, mas principalmente em como a música pode ser usada como ferramenta de ensino de vocabulário pelos professores. Ensinar através de atividades com música permite contextualizar e dar sentido ao aprendizado, pois o aluno perceberá que a música, ele está estudando na escola é o mesmo que ouve na rádio ou na televisão, que a língua inglesa não é mais um sentido importam. A metodologia utilizada neste trabalho foi descritiva, com o objetivo principal de descrever como o professor pode usar a música para ensinar novo vocabulário. A discussão mostra que a música pode ser uma ótima ferramenta para combinar diversão e aprendizado, especialmente considerando a realidade das escolas públicas no Brasil (sic).
Keywords: English language; Music; Vocabulary; Teenagers